Molecular docking study of fatty acids from Pliek U Oil in the inhibition of SARS-CoV-2 protein and enzymes. Issue 1 (February 2021) - Khairan, K; Idroes, R; Tumilaar, S G; Tallei, T E; Idroes, G M; Rahmadhany, F; Futri, M U; Dinura, N M; Mauliza, S; Diana, M; Maisarah, C P; Maulana, A; et al.
Abstract: This study aimed to analyze the fatty acid inPliek U oil andevaluate its inhibitor potential based on the interaction to several proteins and enzymes in SARS-CoV-2 using the in silico approach. Pliek U oil containing capric acid, caprylic acid, lauric acid, linoleic acid, myristic acid, oleic acid, and palmitic acids, with oleic acid as a dominant substance. Molecular docking analysis showed that linoleic acid has the best interaction to the receptors with the lowest binding affinity to 3CLpro (6LU7), Spike protein (6VXX), PLpro (6WX4), RdRp (6M71), E protein (5X29), and Spike Ectodomain Structure (6VYB) of -4.9, -5.8, -4.7, -4.3, -5.3 and -5.5 kcal/mol, respectively. The finding suggests that the binding of linoleic acid to the SARS-CoV-2 protein and enzyme may cause impairment of viral attachments to host cells, thus reducing infectivity in COVID-19 patients.